2017
DOI: 10.1002/jsfa.8441
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprints of resistant Escherichia coli O157:H7 from vegetables and environmental samples

Abstract: BACKGROUND: Some routes of transmission of Escherichia coli O157:H7 to fresh produce include contaminated irrigation water and manure polluted soils. The aim of the present study was to determine the genetic relationships of E. coli O157:H7 isolated from some produce growing region in Nigeria using enterobacterial repetitive intergenic consensus (ERIC) DNA fingerprinting analysis. A total of 440 samples comprising leafy greens, irrigation water, manure and soil were obtained from vegetable producing regions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In the edible part of corn, E. coli was not isolated, and the bla and uidA genes were not detected. Although crops could be contaminated by pathogenic E. coli suspected to be livestock-associated from soil [32,33], the phyllosphere, endosphere, and soil microbiota were quite different [34,35], and the degree of bacterial transmission and persistence from soil to crops would vary according to the type of vegetable [36]. Another study showed that ARGs were transmitted into plants mainly through endophytic bacteria [37].…”
Section: Plos Onementioning
confidence: 99%
“…In the edible part of corn, E. coli was not isolated, and the bla and uidA genes were not detected. Although crops could be contaminated by pathogenic E. coli suspected to be livestock-associated from soil [32,33], the phyllosphere, endosphere, and soil microbiota were quite different [34,35], and the degree of bacterial transmission and persistence from soil to crops would vary according to the type of vegetable [36]. Another study showed that ARGs were transmitted into plants mainly through endophytic bacteria [37].…”
Section: Plos Onementioning
confidence: 99%
“…Previously, fingerprints of resistance Escherichia coli O157:H7 from vegetables and environmental samples from wastewater reuse in irrigation in Nigeria were reported 8 . Sustainable wastewater reuse should prevent both types of effects, requiring a holistic and integrated risk assessment 9 .…”
Section: Introductionmentioning
confidence: 99%